2012
DOI: 10.3727/096368912x638892
|View full text |Cite
|
Sign up to set email alerts
|

Achilles Tendon Regeneration can be Improved by Amniotic Epithelial Cell Allotransplantation

Abstract: Amniotic epithelial cells (AECs) are ideal seed cells for tissue regeneration, but no research has yet been reported on their tendon regeneration potential. This study investigated the efficiency of AEC allotransplantation for tendon healing, as well as the mechanism involved. To this aim ovine AECs, characterized by specific surface and stemness markers (CD14-, CD49f, CD29, CD166, OCT4, SOX2, NANOG, TERT), were allotransplanted into experimentally induced tissue defects in sheep Achilles tendon. In situ tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
131
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(143 citation statements)
references
References 67 publications
4
131
0
1
Order By: Relevance
“…Similar to our result, Barboni et al 12 observed, in Achilles tendon, that immature collagen fibers were completely replaced by mature ones in 28 days. And, stated that the increase in maturity of tendon was due to the stimulus induced by cells derivate from amniotic membrane, which provide a positive paracrine environment, thus accelerating the recovery of normal tendon microstructure and biomechanical properties.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Similar to our result, Barboni et al 12 observed, in Achilles tendon, that immature collagen fibers were completely replaced by mature ones in 28 days. And, stated that the increase in maturity of tendon was due to the stimulus induced by cells derivate from amniotic membrane, which provide a positive paracrine environment, thus accelerating the recovery of normal tendon microstructure and biomechanical properties.…”
supporting
confidence: 81%
“…Organization of the collagen fibers was used to generate a score in order to evaluate the alignment of these fibers in the different groups and experimental times based on the score system used by Barboni et al 12 . The analysis was made on the injured tendon area with an increase of x20, totaling 5 samples per group of all experimental times studied.…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The opportune time of implantation, together with the higher plasticity and proliferative capacity of AMCs compared to BM-MSCs [8], represents the main features of interest for this novel heterologous approach for the treatment of equine tendon diseases. In addition, recent studies of in vivo transplantation of ovine amniotic membrane-derived epithelial cells into the ovine Achilles tendon [12] or into spontaneous equine tendon injuries [13], demonstrated production of ovine collagen, thereby supporting the possibility of applying amniotic epithelial cells for tenocyte regeneration. In regard to the use of MSCs, it is still unclear as to whether the major contribution of MSCs to the tendon-healing process is through their ability to differentiate into tenocytes, whether they instead act mainly to supply immunomodulatory and trophic factors [14,15], or whether a combination of these two mechanisms occurs [16,17].…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, these cells can be stored thanks to cryopreservation and used for allogeneic transplantation in veterinary medicine. Previous experimental studies, in mechanically-induced acute tendon injuries in large animals species (sheep), have shown their good tolerance by the host, due to their low immunologic potential, and their efficacy in regenerating tendon 6,17 . Very good clinical results have been also obtained after transplantation into equine SDF acute tendinopathies, with restoration of a quite normal US pattern of tendon fibers orientation 17 Amniotic epithelial cell and tendinopathy: ultrasound and histological results In the regenerating area a higher nuclei concentration and a lower density of the extracellular matrix fibers in comparison with the healthy tendon are evident.…”
Section: Discussionmentioning
confidence: 99%